2019
DOI: 10.1167/iovs.19-26728
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of LSD1 Expression Within the Murine Eye

Abstract: The purpose of this study was to extend the current understanding of endogenous lysine-specific demethylase 1 (LSD1) expression spatially and temporally in the retina. Toward that end, we determined the localization and levels of LSD1 and its substrates H3K4me1 and H3K4me2 (H3K4me1/2) within the murine eye. METHODS. Immunofluorescent microscopy for LSD1, H3K4me1, and H3K4me2 was conducted on murine formalin-fixed paraffin-embedded eye sections across development in addition to Western immunoblotting to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…#Fisher BP2401-500) at −80 °C for 4 days, embedded in paraffin, and sectioned through the sagittal plane on a microtome at thickness of 5 µm, with minor variation of the freeze-substitution method of Mary-Sinclair et al 28 Sections were used for hematoxylin and eosin staining, as described previously. 29 All sections were imaged with a bright-field microscope with a 20× objective.…”
Section: Methodsmentioning
confidence: 99%
“…#Fisher BP2401-500) at −80 °C for 4 days, embedded in paraffin, and sectioned through the sagittal plane on a microtome at thickness of 5 µm, with minor variation of the freeze-substitution method of Mary-Sinclair et al 28 Sections were used for hematoxylin and eosin staining, as described previously. 29 All sections were imaged with a bright-field microscope with a 20× objective.…”
Section: Methodsmentioning
confidence: 99%
“…The distribution of LSD1 matched the cell- and stage-specific patterns of H3K4 methylation during male germ cell differentiation ( 57 ). Furthermore, initiation of LSD1 expression induced the differentiation of some retinal progenitor cells (RPCs), suggesting that LSD1 was highly and uniformly expressed in the eye of mouse and played a critical role in the differentiation of RPCs ( 58 ). In this study, the mRNA transcripts of Cg LSD1 were widely detected in all the tested tissues with the highest expression level in the mantle and a relatively higher expression level in hemocytes.…”
Section: Discussionmentioning
confidence: 99%
“…LSD1 knockdown could inhibit cancer or disease development, and thus it is an attractive target for providing novel therapeutics. [37][38][39] It has been reported that LSD1 served as a negative regulator of osteogenesis. 28 Likewise, in our study, we discovered that the mRNA and protein expression of LSD1 were obviously upregulated both in OVX mice and under MG. LSD1 deficiency facilitated osteogenic differentiation while suppressed apoptosis in MC3T3-E1 cells under simulated MG.…”
Section: Discussionmentioning
confidence: 99%